ChemInform Abstract: Access to a New Class of Synthetic Building Blocks via Trifluoromethoxylation of Pyridines and Pyrimidines. Issue 18 (April 2016) - Feng, Pengju; Lee, Katarzyna N.; Lee, Johnny W.; Zhan, Chengbo; Ngai, Ming‐Yu
Abstract: A broad spectrum of differently substituted pyridines and some pyrimidines are treated with Togni reagent I (II) to produce derivatives bearing the important ‐O‐CF3 function.